Digital-Based Information System of Zakat Management in Indonesia: Strategies for Increasing Revenue in Fiqh Muamalah Perspectives - Musa, Armiadi; Zulfikar, Teuku; Khalidin, Bismi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This study aims to examine the digital-based zakat management information system and strategies for increasing ZIS fund income from the perspective of muamalah fiqh in NTB and Aceh. This study focuses on using SimBaznas on the loyalty of zakat payments, the cand constraints, and strategies taken to increase zakat payments in the two regions. This is a mixed-method study to obtain more comprehensive, reliable, and objective data. The results showed that the implementation of SimBaznas at Baznas in NTB was only carried out on reporting zakat collection that had been carried out properly, while reports and asset reports had not been well informed in SimBaznas. Meanwhile, in Aceh Province, all SimBaznas features have not been effective. Quantitative analysis shows that the ease of use and availability of facilities and infrastructure does not guarantee a correlation with the implementation of SimBaznas in the two provinces. In addition, the seriousness of the interest of SimBaznas users has an effective effect on the implementation of the system. However, it is certain that the existence of SimBaznas has no significant effect on the loyalty of Muslims in the two provinces. The problem with using SimBaznas is caused by the lack of quantity and quality of IT-based human resources. Therefore, the strategies that can be applied are improving the quality and quantity of SimBaznas IT managers, socializing SimBaznas to the public, encouraging ratifying the law on zakat as a tax deduction, and finalizing the regulation of zakat as PAD in Aceh. Therefore, in the context of fiqh muamalah, Baitul Mal will increasingly contribute to poverty alleviation, economic development, and human resource development in NTB, Aceh, and Indonesia.